Optimization of travelling salesman problem with precedence constraint using modified GA encoding - M. F. F., Ab Rashid; N. M. Zuki, N. M.; F. R. M., Romlay; M., Jusop (American Scientific Publishers, 2018)
One of the challenges in combinatorial optimization is to optimize travelling salesman problem with precedence constraint (TSPPC). The optimization algorithm to deal with this problem is continuously developed and improved to enhance its performance. Genetic algorithm (GA) is one of popular algorithm used to optimize TSPPC. In this work, the Genetic algorithm is improved by using a discrete encoding instead of continuous encoding. The numerical experimental results indicated that the proposed algorithm able to search for optimal solution faster compared with original encoding.